(untitled) (Bangladesh Journal of Botany, 2026)
Plants of the family Convolvulaceae are known for their medicinal properties and diverse phytochemical profiles. This study compared five native species of Bangladesh: Evolvulus glomeratus (Choisy) Nees and Mart., Ipomoea batatas (L.) Lam., I. cairica (L.) Sweet, I. quamoclit L., and I. aquatica Forssk. The analysis examined chlorophyll, carotenoids, anthocyanins, flavonoids, phenolics, tannins, proline contents, and antioxidant capacity. The results revealed significant variations among the species. Evolvulus glomeratus exhibited the highest levels of chlorophyll a (2.12 mg/g FW), total chlorophyll (2.65 mg/g FW), total phenolic (6.62 mg eq. GAE/100g FW), total flavonoid (6.41 mg eq. QUE/100g FW), tannin (4.63 mg/g FW), and antioxidant capacity (6.68 mg eq. AA/g FW). In contrast, I. cairica showed the lowest levels for chlorophyll a (0.47 mg/g FW), chlorophyll b (0.25 mg/g FW), total chlorophyll (0.72 mg/g FW), total carotenoids (0.94 mg/g FW), and total flavonoids (3.04 mg QE/g FW). This study emphasizes the phytochemical diversity of the Convolvulaceae family and its potential for nutraceutical and pharmaceutical applications, suggesting that future research should isolate specific compounds to assess their pharmaceutical potential. Bangladesh J. Bot. 55(2): 303-309, 2026 (June)